Tic62: a protein family from metabolism to protein translocation - Soll Jürgen; Stengel Anna; Balsera Mónica; Bölter Bettina (BMC Evolutionary Biology, 2007)
Abstract Background The function and structure of protein translocons at the outer and inner envelope membrane of chloroplasts (Toc and Tic complexes, respectively) are a subject of intensive research. One of the proteins that have been ascribed to the Tic complex is Tic62. This protein was proposed as a redox sensor protein and may possibly act as a regulator during the translocation process. Tic62 is a bimodular protein that comprises an N-terminal module, responsible for binding to pyridine nucleotides, and a C-terminal module which serves as a docking site for ferredoxin-NAD(P)-oxido-reductase (FNR). This work focuses on evolutionary analysis of the Tic62-NAD(P)-related protein family, derived from the comparison of all available sequences, and discusses the structure of Tic62. Results Whereas the N-terminal module of Tic62 is highly conserved among all oxyphototrophs, the C-terminal region (FNR-binding module) is only found in vascular plants. Phylogenetic analyses classify four Tic62-NAD(P)-related protein subfamilies in land plants, closely related to members from cyanobacteria and green sulphur bacteria. Although most of the Tic62-NAD(P)-related eukaryotic proteins are localized in the chloroplast, one subgroup consists of proteins without a predicted transit peptide. The N-terminal module of Tic62 contains the structurally conserved Rossman fold and probably belongs to the extended family of short-chain dehydrogenases-reductases. Key residues involved in NADP-binding and residues that may attach the protein to the inner envelope membrane of chloroplasts or to the Tic complex are proposed. Conclusion The Tic62-NAD(P)-related proteins are of ancient origin since they are not only found in cyanobacteria but also in green sulphur bacteria. The FNR-binding module at the C-terminal region of the Tic62 proteins is probably a recent acquisition in vascular plants, with no sequence similarity to any other known motifs. The presence of the FNR-binding domain in vascular plants might be essential for the function of the protein as a Tic component and/or for its regulation.